An Examination of The Challenges Associated with Olfactory Stimuli in Museum Services: A Systematic Review of Visitor-Centric Strategies - Malc, Domen; Rakuša, Nika; Milfelner, Borut; Pisnik, Aleksandra (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
This systematic review examines the impact of olfactory stimuli in museums, revealing a gap in the literature on how scents enhance visitor experiences. Utilising the PRISMA methodology, we analysed 237 records from various academic databases. Findings illustrate that scents are often thematically aligned with exhibits, such as historical scents, to deepen visitor engagement. Art galleries also utilise scents to enhance emotional and cognitive responses, evoking memories and enhancing immersion. Both pleasant and unpleasant scents impact visitors: pleasant scents improve mood and engagement, while unpleasant scents can intensify emotional reactions and immersion. Nevertheless, challenges like olfactory fatigue and technical limitations in scent delivery can hinder effectiveness. Overuse or weak diffusion may detract from the intended experience. Multisensory approaches that combine scent with other stimuli are especially beneficial for inclusivity, particularly for visually impaired visitors. Yet the review also identifies methodological limitations in current research, including small sample sizes, limited demographic diversity, and laboratory-based settings. The absence of standardised guidelines makes consistent integration difficult. Overall, this review highlights the potential of olfactory elements to enrich museum experiences and encourages further exploration and innovation in integrating olfactory stimuli into cultural experiences, including via a customer-centric lens.